Antagonizing microRNA‐19a/b augments PTH anabolic action and restores bone mass in osteoporosis in mice. Issue 11 (4th October 2022) - Taipaleenmäki, Hanna; Saito, Hiroaki; Schröder, Saskia; Maeda, Miki; Mettler, Ramona; Ring, Matthias; Rollmann, Ewa; Gasser, Andreas; Haasper, Carl; Gehrke, Thorsten; Weiss, Alexander; Grimm, Steffen K; et al.
Abstract: Postmenopausal bone loss often leads to osteoporosis and fragility fractures. Bone mass can be increased by the first 34 amino acids of human parathyroid hormone (PTH), parathyroid hormone‐related protein (PTHrP), or by a monoclonal antibody against sclerostin (Scl‐Ab). Here, we show that PTH and Scl‐Ab reduce the expression of microRNA‐19a and microRNA‐19b (miR‐19a/b) in bone. In bones from patients with lower bone mass and from osteoporotic mice, miR‐19a/b expression is elevated, suggesting an inhibitory function in bone remodeling. Indeed, antagonizing miR‐19a/b in vivo increased bone mass without overt cytotoxic effects. We identified TG‐interacting factor 1 (Tgif1) as the target of miR‐19a/b in osteoblasts and essential for the increase in bone mass following miR‐19a/b inhibition. Furthermore, antagonizing miR‐19a/b augments the gain in bone mass by PTH and restores bone loss in mouse models of osteoporosis in a dual mode of action by supporting bone formation and decreasing receptor activator of NF‐κB ligand (RANKL)‐dependent bone resorption. Thus, this study identifies novel mechanisms regulating bone remodeling, which opens opportunities for new therapeutic concepts to treat bone fragility. Synopsis: Due to low bone mass, osteoporosis leads to fractures. Current drugs increase bone mass but have limitations. Thus, additional medicines are needed. Here we established anti‐sense oligonucleotide‐based microRNA‐19a/b inhibition to increase bone mass in osteoporosis by a novel dual mode of action. Post‐menopausal osteoporosis is caused by an increased osteoclast‐dependent bone resorption and a reduced osteoblast‐mediated bone formation often leading to fragility fractures that are associated with an increased morbidity and mortality. Patients with osteoporosis are frequently treated with anti‐resorptive drugs or anabolic agents such as PTH 1‐34 or an anti‐sclerostin antibody to increase bone mass. We uncovered that PTH 1‐34 and an anti‐sclerostin antibody reduced the expression of microRNA‐19a and microRNA‐19b (miR‐19a/b) in bone. Human bones with lower bone mass and bones from osteoporotic mice displayed an increased miR‐19a/b expression. Anti‐sense oligonucleotide‐mediated miR‐19a/b inhibition augmented the PTH 1‐34‐induced gain in bone mass and reconstituted low bone mass in osteoporosis in mice by supporting bone formation and decreasing bone resorption. Abstract : Due to low bone mass, osteoporosis leads to fractures. Current drugs increase bone mass but have limitations. Thus, additional medicines are needed. Here we established anti‐sense oligonucleotide‐based microRNA‐19a/b inhibition to increase bone mass in osteoporosis by a novel dual mode of action.